Identification of the novel HLA‐B*15:257 allele by polymerase chain reaction sequence‐based typing in a Chinese individual. Issue 1 (24th April 2013) - Han, Z.‐D.; Zhang, W.; Zhu, F.‐M.; He, J.; Lv, H.‐J.
Abstract : HLA‐B*15:257 has one nucleotide change in exon 2 at position 232C>G from B * 15:01:01:01 .